Olfactory responsiveness of Culex quinquefasciatus and Aedes albopictus (Diptera: Culicidae): Interactions between species, age and attractants - Andrea DRAGO (Institute of Entomology, Biology Centre, Czech Academy of Science, 2021)
Invasive mosquitoes are vectors of important human and animal pathogens and a serious threat to public health. Aedes albopictus (Skuse) (Diptera: Culicidae) and Culex quinquefasciatus (Say) (Diptera: Culicidae) are good examples because of their wide occurrence, host range and vector competence. An understanding of the responsiveness of mosquitoes to olfactory stimuli is essential for implementing effective surveillance and developing repellents. The present study evaluated the behavioural responses of A. albopictus and C. quinquefasciatus to CO2 and human skin odour in an olfactometer. In addition, CO2 synergistic effect was assessed in association with human skin odour. Mosquitoes of different ages (3-5 and 10-15 day old) were included in the study in order to determine changes in responsiveness to attractants during an insects' lifetime. The highest numbers of mosquitoes captured associated with CO2 were (A. albopictus, 48/77, 62.34%; C. quinquefasciatus, 117/126, 92.86%) and hand odour (A. albopictus, 211/232, 90.95%; C. quinquefasciatus, 320/374, 85.56%) in the "CO2 vs blank" and "hand vs blank" treatments. Skin odour was the most attractive for both species (A. albopictus, 279/309, 90.29%; C. quinquefasciatus, 292/306, 95.42%) in "CO2 vs hand" experiment. The highest mosquito responsiveness was recorded in the "CO2 + hand vs hand" bioassay (A. albopictus, 174/265, 65.66%; C. quinquefasciatus, 231/425, 54.35%). Similar trends were recorded for 10-15 and 3-5 day old mosquitoes of both species in all the experiments. In addition, a linear mixed model was used to evaluate the interactions between species, age and attractants. Human skin odour and CO2 were effective attractants for both A. albopictus and C. quinquefasciatus (attractant-species interaction, p-value < 0.05). CO2 synergistic effect was recorded for both species (species-attractant interaction, p-value < 0.05) even when CO2 was not directly combined with skin odour (p-value < 0.05). The interaction between attractant and age revealed (p-value < 0.05) that in both species, 10-15 day old mosquitoes were more responsive to CO2 and human skin odour, than younger (3-5 days) adults. The species-age interaction (p-value < 0.05) showed that 3-5 and 10-15 day old C. quinquefasciatus were more receptive to CO2 and skin odour, especially when used in combination, than A. albopictus.